Policy Strategies to Reduce Waiting Times for Elective Surgery: A Scoping Review and Evidence Synthesis - Bachelet-Norelli, V (John Wiley and Sons Ltd, 2019)
Objectives: The purpose of this evidence-based review is to identify and describe the interventions that have been implemented to reduce waiting times for major elective surgery. Methods: Scoping review and presentation of the results according to the SUPPORT tools. We searched MEDLINE/PubMed, Embase, Cochrane Library, SciELO, DARE-HTA, and Google Scholar. The inclusion criteria for research design were comprehensive. Results: We identified 5200 records. After eliminating duplicates and screening by title and abstract, 171 records remained for full-text assessment, of which 12 were ultimately included for this review because they reported specific interventions and 96 records were included for further reference. The included studies show significant variability regarding elective procedures, population, and type of provider, as well as in the characteristics of the interventions and the settings. All the studies had methodological limitations. We graded the certainty of the evidence as very low. Conclusions: According to the evidence found for this review, interventions most likely should be multidimensional, with prioritization strategies on the waiting lists to incorporate equity criteria, together with quality management improvements of the surgical pathways and the use of operating rooms, as well as improvements in the planning of the surgical schedule. © 2019 John Wiley & Sons, Ltd.